Range change evolution of peat mosses (Sphagnum) within and between climate zones. (15th November 2018) - Shaw, A. Jonathan; Carter, Benjamin E.; Aguero, Blanka; da Costa, Denise Pinheiro; Crowl, Andrew A.
Abstract: Peat mosses ( Sphagnum ) hold exceptional importance in the control of global carbon fluxes and climate because of the vast stores of carbon bound up in partially decomposed biomass (peat). This study tests the hypothesis that the early diversification of Sphagnum was in the Northern Hemisphere, with subsequent range expansions to tropical latitudes and the Southern Hemisphere. A phylogenetic analysis of 192 accessions representing the moss class Sphagnopsida based on four plastid loci was conducted in conjunction with biogeographic analyses using BioGeoBEARS to investigate the tempo and mode of geographic range evolution. Analyses support the hypothesis that the major intrageneric clades of peat‐forming species accounting for >90% of peat moss diversity originated and diversified at northern latitudes. The genus underwent multiple range expansions into tropical and Southern Hemisphere regions. Range evolution in peat mosses was most common within latitudinal zones, attesting to the relative difficulty of successfully invading new climate zones. Allopolyploidy in Sphagnum (inferred from microsatellite heterozygosity) does not appear to be biased with regard to geographic region nor intrageneric clade. The inference that Sphagnum diversified in cool‐or cold‐climate regions and repeatedly expanded its range into tropical regions makes the genus an excellent model for studying morphological, physiological, and genomic traits associated with adaptation to warming climates. Abstract : This study tests the hypothesis that Sphagnum (peat mosses) initially diversified at high latitudes of the Northern Hemisphere and later extended their ranges to tropical and Southern Hemisphere regions. The ancestral geographic area for the genus as a whole is ambiguous, but the four major subgenera, comprising some 90% of the generic species diversity, unambiguously originated at high latitudes. Sphagnum provides a model for research on genomic, ecological, and morphological changes associated with adaptation to warm climates from cold or cool climate ancestors.